Promoter opening via a DNA fork junction binding activity - Guo, Yuli (National Academy of Sciences, 1998)
The rate-limiting step in transcriptional initiation typically is opening the promoter DNA to expose the template strand. Opening is tightly regulated, but how it occurs is not known. These experiments identify an activity, recognition of specific DNA fork junctions, and suggest that it is critical to bacterial promoter opening. This activity is both sequence and structure specific; it recognizes the bases that constitute the upstream double-stranded/single-stranded boundary of the open complex. Promoter mutations known to reduce opening rates lead to comparable reductions in fork junction binding affinity. The activity acts to establish the upstream boundary of melted DNA and works in conjunction with two single-stranded DNA binding activities that recognize separately the two melted strands. The junction binding activity is contained within the sigma factor component of the holoenzyme. The activity occurs in both a typical prokaryotic transcription system and in a eukaryotic-like bacterial system that responds to enhancers and needs ATP. Thus DNA opening catalyzed by fork junction binding may occur in a variety of systems in which DNA must be opened to be copied.